2017
DOI: 10.1371/journal.pntd.0005654
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito co-infection with Zika and chikungunya virus allows simultaneous transmission without affecting vector competence of Aedes aegypti

Abstract: BackgroundZika virus (ZIKV) and chikungunya virus (CHIKV) are highly pathogenic arthropod-borne viruses that are currently a serious health burden in the Americas, and elsewhere in the world. ZIKV and CHIKV co-circulate in the same geographical regions and are mainly transmitted by Aedes aegypti mosquitoes. There is a growing number of case reports of ZIKV and CHIKV co-infections in humans, but it is uncertain whether co-infection occurs via single or multiple mosquito bites. Here we investigate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
143
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 45 publications
(60 reference statements)
20
143
1
2
Order By: Relevance
“…In their study, Aedes albopictus was orally infected with both Dengue and Chikungunya viruses with an ability to transmit them to their human host via its saliva. A study by Göertz et al (2017); where Aedes aegypti were orally infected by Chikungunya and Zika viruses reported similar results and the vectors were highly competent, with transmission rates of up to 73% for ZIKV, 21% for CHIKV, and 12% of mosquitoes transmitting both viruses in one bite.…”
Section: Resurgence or Emergence Of Epidemic Arboviral Diseasesmentioning
confidence: 71%
See 4 more Smart Citations
“…In their study, Aedes albopictus was orally infected with both Dengue and Chikungunya viruses with an ability to transmit them to their human host via its saliva. A study by Göertz et al (2017); where Aedes aegypti were orally infected by Chikungunya and Zika viruses reported similar results and the vectors were highly competent, with transmission rates of up to 73% for ZIKV, 21% for CHIKV, and 12% of mosquitoes transmitting both viruses in one bite.…”
Section: Resurgence or Emergence Of Epidemic Arboviral Diseasesmentioning
confidence: 71%
“…However, their reports are conflicting on the aspect of vector competence. Göertz et al (2017) reported co-infection of Zika and Chikungunya virus does not influence vector competence in Aedes aegypti. In contrast, report by Rückert et al (2017) says infection, dissemination and transmission of viruses by Aedes aegypti is mildly affected by co-infections of Zika, Chikungunya and Dengue viruses.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations